IMPLEMENTASI PERATURAN DESA MAJASARI NOMOR 3 TAHUN 2012 TENTANG PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) ASAL DESA MAJASARI - Iqbal Bachtiar Guntara; Lena Satlita (NATAPRAJA, 2017)
This research aims to analyze the implementation of policy the protection of indonesian labor Majasari in Majasari village, Indramayu and the policy barriers. This research  used  descriptive  approach  with qualitative methods. This technique of data collection is done by way of interview, observation and documentation. An examination of the validity of the data is done by triangulation of sources. The data analysis process includes the collection of data, data presentation, data reduction and withdrawal of the conclusion. The results showed that the implementation of the policy of Indonesian labor protection in the village of Majasari is not yet running to its full potential. Protection undertaken include pre placement, placement, full-time placement and full empowerment and family labor indonesia abandoned integrated. Barriers in the implementation  of  this policy  related  to  budget  that  never  noted  in  the  budget  revenue  and expenditure of the village Majasari, a limited number of employees of the village, the absence of mentoring on a full-time business group of Indonesian labor Majasari, low awareness of candidates and after Indonesian labor as well as the implementing party of Labor Placement Private report to the Government of Indonesia village, trouble filling the pregnancy and childbirth on the cow.Keyword: Early Marriage, Population Policy, and Sleman District